Multiple paths of midlife development - Lachman, Margie E.; James, Jacquelyn Boone (Studies on successful midlife development, 1997)
In this collection of fifteen papers, leading researchers analyze the middle years of the lifespan, paying close attention to the many different facets of adult development. They study the various changes involving the self and others that middle-aged adults experience in the realms of work, family, and health. This book explains how the different experiences interrelate and how a better understanding of them can foster successful midlife development.